(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This study is in the context of studies that use advanced software applications to solve problems, which are difficult to be solved with statistical and mathematical tools. Simulation models were used using the Arena program in an attempt to build simulation models for the Popular Credit Bank in Tartous with its productive and limited income branches. These models reflect the flow of customers on these branches and their receive of banking services. It also measures a number of variables such as processing times of banking services and waiting times for customers in Queue, as well as human resource utilization rates, in order to infer a gap between the supply and demand on the services of this bank . The study concluded that: There is a high demand for Popular Credit Bank services, and that the number of employees in the bank is not increased enough to meet the growth of this demand, as well as the procedures followed for the implementation of banking operations are long and overcome the paper cycle of the electronic one. All these led to the formation of long queues indicate: There are deficiencies in covering the services offered by this bank to the demand تندرج هذه الدراسة في سياق الدراسات التي تستخدم تطبيقات برمجية متطورة لحل مشكلات صعبة الحل بالأدوات الإحصائية والرياضية اليدوية. إذ تمت الاستعانة بنماذج المحاكاة باستخدام برنامج "Arena" في محاولة لبناء نموذج محاكاة لمصرف التسليف الشعبي في طرطوس بفرعيه الإنتاجي والدخل المحدود. هذا النموذج يجسد افتراضياً الواقع من حيث تدفق العملاء على هذه الفروع وتلقيهم للخدمات المصرفية, كما يقيس عدد من المتغيرات كأزمنة إنجاز العمليات المصرفية وأزمنة الانتظار للعملاء في صفوف الانتظار ومعدلات استخدام الموارد البشرية, كل ذلك بهدف الاستدلال على وجود فجوة بين العرض والطلب على خدمات هذا المصرف. توصلت الدراسة إلى: وجود حجم طلب كبير على خدمات مصرف التسليف الشعبي, وأن أعداد العاملين لا يتم زيادتها في المصرف بمستوى كافي لمقابلة نمو هذا الطلب, وأن الإجراءات المتبعة لتنفيذ العمليات المصرفية طويلة وتغلب فيها الدورة المستندية على الالكترونية, كل ذلك أدًى إلى تشكل صفوف انتظار طويلة تدل على وجود قصور في مقابلة عرض خدمات هذا المصرف للطلب عليها.